Creating a circuit training model to improve the agility of seven-year-olds - Tatok Sugiarto; Arief Darmawan; Zihan Novitasari; Nadia Milkhatun Nadlifah; Primita Nur Mazzidah (CV Rezki Media, 2022)
The objective of this study is to create an efficient circuit training model for 7-year-old kids. Research and development from borg and gall are the research methods used. There are 24 variations as a result of this research and development. Four training posts were developed by researchers, each of which tries to train one or two aspects of physical fitness. Strength, Endurance, Muscular Power, Speed, Flexibility, Agility, Coordination, and Balance are the 10 elements of physical fitness. Following a review of the literature on the characteristics of children aged 7 years, the researchers only created 4 posts, each of which may train one to two physical fitness components. On elementary school pupils in grade 1, this circuit training model's development and research were tested. The test results can be correctly implemented. Following the phases of study and development, it has been determined that this model can be used in schools.